Can lean contribute to work intensification in healthcare?. Issue 3 (15th May 2017) - Rees, Gareth H.; Gauld, Robin
Abstract : Purpose: The purpose of this paper is to review and discuss the effects of the introduction of lean into healthcare workplaces, phenomena that have not been widely investigated. Design/methodology/approach: The paper draws on discussions and findings from the literature. It seeks to bring the few geographically dispersed experiences and case studies together to draw some conclusions regarding lean's negative effects. Findings: Two recurring themes emerge. The first is there is little evidence of Lean's impact on work and the people who perform it. The literature therefore suggests that we understand very little about how work conditions are changed and how Lean's negative effects arise and may be managed in healthcare workplaces. A second observation is that Lean's effects are ambiguous. For some Lean seems to intensify work, while for others it leads to improved job satisfaction and productivity. Given this variety, the paper suggests a research emphasis on Lean's socio-cultural side and to derive more data on how work and its processes change, particularly in the context of healthcare team-working. Originality/value: The paper concludes that without improved understanding of social contexts of Lean interventions its value for healthcare improvement may be limited. Future research should also include a focus on how the work is changed and whether high-performance work system practices may be used to offset Lean's negative effects.